Acropora interbranch skeleton Sr/Ca ratios: Evaluation of a potential new high‐resolution paleothermometer. (30th April 2016) - Sadler, James; Nguyen, Ai D.; Leonard, Nicole D.; Webb, Gregory E.; Nothdurft, Luke D.
Abstract: The majority of coral geochemistry‐based paleoclimate reconstructions in the Indo‐Pacific are conducted on selectively cored colonies of massive Porites . This restriction to a single genus may make it difficult to amass the required paleoclimate data for studies that require deep reef coring techniques. Acropora, however, is a highly abundant coral genus in both modern and fossil reef systems and displays potential as a novel climate archive. Here we present a calibration study for Sr/Ca ratios recovered from interbranch skeleton in corymbose Acropora colonies from Heron Reef, southern Great Barrier Reef. Significant intercolony differences in absolute Sr/Ca ratios were normalized by producing anomaly plots of both coral geochemistry and instrumental water temperature records. Weighted linear regression of these anomalies from the lagoon and fore‐reef slope provide a sensitivity of −0.05 mmol/mol °C −1, with a correlation coefficient ( r 2 = 0.65) comparable to those of genera currently used in paleoclimate reconstructions. Reconstructions of lagoon and reef slope mean seasonality in water temperature accurately identify the greater seasonal amplitude observed in the lagoon of Heron Reef. A longer calibration period is, however, required for reliable reconstructions of annual mean water temperatures. Key Points: Seasonal cycles were observed in Sr/Ca ratios of Acropora interbranch skeleton No significant correlation was observed between linear extension and interbranch Sr/Ca ratios Acropora interbranch skeleton Sr/Ca anomaly ratios can be effectively used to reconstruct changes in mean seawater temperature seasonality